Определение характеристик в зацеплении зубчатых колес, нарезаемых методом обката - Павлов, А. И.; Павлов, В. А.; Протасов, Роман Васильевич (НТУ "ХПИ", 2009)
Отримані залежності для визначення якісних характеристик зубців з різноманітними зачепленнями. Вони можуть застосовуватися при дослідженнях зачеплень із випукло-вогнутим контактом.

In clause formulas for definition of qualitative characteristics of tooth gearings with any gearing are resulted. Factors of overlapping, the specific sliding, the resulted radius of curvature in gearing of teeth are considered. Restrictions to make teeth as thin and maintenance of convexo-concave contact are imposed.
Keywords: нарезание зубьев; параметры зубьев; число зубьев; коэффициент разновидности; качественные характеристики